(untitled) (Triwikrama: Jurnal Ilmu Sosial, 2025)
This study aims to identify the stages of social intervention implemented in improving children’s welfare at the Cinta Kasih Medan Orphanage. Social intervention is a systematic effort carried out by social workers, social welfare institutions, and the community to support the physical, psychological, social, and spiritual development of children in care. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with caregivers, children in the orphanage, and supporting documents from the foundation.The results of the study indicate that the stages of social intervention at the Cinta Kasih (1) Orphanage include: identifications of children problem and needs; and (2) Implementation of intervention programs such as tutoring, and life skills training; and (3) Evaluation and follow-up. The intervention has a positive impact on increasing children’s selfconfidence academic ability, and social integration. However, challenges such as limited human resources and funding are still obstacles to optimal implementation of the intervention. This study recommends increasing the capacity of caregivers and broader collaboration with external parties to support the sustainability of the intervention program.